2011
DOI: 10.1002/psc.1416
|View full text |Cite
|
Sign up to set email alerts
|

Interference of low‐molecular substances with the thioflavin‐T fluorescence assay of amyloid fibrils

Abstract: Abnormal fibrillization of amyloidogenic peptides/proteins has been linked to various neurodegenerative diseases such as Alzheimer's and Parkinson's disease as well as with type-II diabetes mellitus. The kinetics of protein fibrillization is commonly studied by using a fluorescent dye Thioflavin T (ThT) that binds to protein fibrils and exerts increased fluorescence intensity in bound state. Recently, it has been demonstrated that several low-molecular weight compounds like Basic Blue 41, Basic Blue 12, Azure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…However, it is still unclear whether acridine inhibited PrP res and quenched ThT at the same time. It has been reported that, in dye-dependent seeded aggregation assays, low molecular weight substances can interfere with the fluorescence of dye compounds bound to amyloid fibrils [27]. Indeed, some compounds have been posited to compete with ThT for the same binding site on fibrils rather than directly inhibit the fibrilization process.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether acridine inhibited PrP res and quenched ThT at the same time. It has been reported that, in dye-dependent seeded aggregation assays, low molecular weight substances can interfere with the fluorescence of dye compounds bound to amyloid fibrils [27]. Indeed, some compounds have been posited to compete with ThT for the same binding site on fibrils rather than directly inhibit the fibrilization process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the authors of (Noormägi et al 2012) showed that some low molecular weight substances (Tannic acid, Basic Blue 41, BB 12, Azure C) can interfere with the ThT assay by decreasing the fluorescence signal of ThT bound to insulin fibrils without inhibiting the insulin fibrillization process. The anionic, but not cationic or neutral, micellar microenvironment of SDS shifts the maximum of ThT absorption from 412 nm in buffer to 428 nm inside the micelle, with an increase in the peak molar absorptivity and a significant (some 13-fold) increase in ThT fluorescence (Kumar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These dyes interactw ith amyloid peptide in the aggregation process, which interferes with in situ measurements, for example Congo Red and Thioflavin T( ThT). [13] Herein, we combined label-free quartz crystal microbalance (QCM), atomic force microscopy (AFM), and circulard ichroism (CD) spectra,t oq uantitativelye xplore the modulating effect of MoS 2 on the fibrillization of two amyloid peptides, Ab (33-42), ak ey hydrophobic fragment of amyloid protein Ab (1-42), [14] and amylin (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), the fibrillating core fragment of the humani slet amyloid polypeptide(hIAPP) involved in type-II diabetes. [15] We obtained MoS 2 suspensionsb yh ydrothermalt reatment of molybdic oxide and KSCN.…”
mentioning
confidence: 99%